ENHANCING HIGH SCHOOL STUDENTS' NUMERACY SKILLS IN 3D POSITIONING THROUGH AUGMENTED REALITY - Yuspira, Lidia; Agustiani, Riza; Zahra, Atika; Putri, Agustiany Dumeva (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study explores a learning trajectory to teach three-dimensional positioning using augmented reality (AR) and assesses students' numeracy literacy skills after using AR-based learning. The research follows a three-stage design research approach: preparation, the design experiment (split into pilot and teaching phases), and retrospective analysis. The study incorporates three AR-based activities in a student worksheet. In the first activity, students observe the AR simulation of a futsal field to identify spatial elements. In the second, they interact with the AR to determine positions in three-dimensional space. In the third, students solve related spatial problems, applying their numeracy skills. The AR-based design aims to enhance students' understanding of three-dimensional positioning for Grade XII high school students and assess improvements in their numeracy literacy through these interactive, structured activities.